Autologous hematopoietic stem cell transplantation improves long-term survival: data from a national registry - Blank, Norbert; Schmalzing, Marc; Moinzadeh, Pia; Oberste, Max; Siegert, Elise; Müller-Ladner, Ulf; Riemekasten, Gabriela; Günther, Claudia; Kötter, Ina; Zeidler, Gabriele; Pfeiffer, Christiane; Juche, Aaron; et al. (Arthritis Research & Therapy, 2022)
Current recommendations on the management of systemic sclerosis (SSc) suggest that autologous hematopoietic stem cell therapy (HSCT) can be a rescue therapy for patients with rapidly progressive SSc. To assess the safety and efficacy of HSCT for patients with SSc and to compare these with non-HSCT patients in a control cohort with adjusted risk factors.